Influence of temperature and humidity on the reproductive efficiency of dairy cattle - John E. Shirley; G.G. Lagombra (Kansas Agricultural Experiment Station Research Reports, 1985)
The reproductive performance of 179 Holstein cows during the period from December 1978 through March 1984 was evaluated with respect to environmental temperature and humidity at the time of insemination. This study was conducted at the Western Kentucky University Farm, Bowling Green, Kentucky. Average monthly temperatures are similar to eastern Kansas, but average humidity is approximately 10 per cent higher. Average seasonal temperature and humidity values during the study period were 37.5°F, 81.2%; 60.2°F, 84.4%; 74.9°F, 89.4%; and 53.6°F, 85.3% for winter, spring, summer and fall, respectively. Conception rates observed were 54%, 46%, 15%, and 39% for winter, spring, summer, and fall, respectively. A complete randomized design was used to determine significant differences among seasonal conception rates and among months within seasons. Conception rates were significantly different (P.05) among months within seasons.; Dairy Day, 1985, Kansas State University, Manhattan, KS, 1985;
Keywords: Kansas Agricultural Experiment Station contribution; no. 86-94-S; Report of progress (Kansas Agricultural Experiment Station); 484; Dairy; Temperature; Humidity; Reproductive efficiency; Performance